2021
DOI: 10.1038/s41598-021-89641-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive SNPs for β0-thalassemia/HbE disease severity

Abstract: Abstractβ-Thalassemia/HbE disease has a wide spectrum of clinical phenotypes ranging from asymptomatic to dependent on regular blood transfusions. Ability to predict disease severity is helpful for clinical management and treatment decision making. A thalassemia severity score has been developed from Mediterranean β-thalassemia patients. However, different ethnic groups may have different allele frequency and linkage disequilibrium structures. Here, Thai β0-thalassemia/HbE disease genome-wild association studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
2
3
0
1
Order By: Relevance
“…The frequency of the two alleles A and C in patients with A (0.56) and C (0.44) as for the control A (0.52) and C (0.48), is illustrated in Table 4 and Figure 3. The results of using ARMS-PCR showed that there are two alleles A and C with three genotypes AA, AC, and CC which are consistent with the previous studies [19,20]. The results of the frequency distribution of the A and C alleles of the BCL11A gene showed that their distribution percentage was not equal among the βthalassemia major patient and control samples, where the A allele percentage in patients was 56%, while in the control it was 52% and the percentage of the C allele was in the patient at 44 % and in the control, it was 48%, as summarized in Table 5.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The frequency of the two alleles A and C in patients with A (0.56) and C (0.44) as for the control A (0.52) and C (0.48), is illustrated in Table 4 and Figure 3. The results of using ARMS-PCR showed that there are two alleles A and C with three genotypes AA, AC, and CC which are consistent with the previous studies [19,20]. The results of the frequency distribution of the A and C alleles of the BCL11A gene showed that their distribution percentage was not equal among the βthalassemia major patient and control samples, where the A allele percentage in patients was 56%, while in the control it was 52% and the percentage of the C allele was in the patient at 44 % and in the control, it was 48%, as summarized in Table 5.…”
Section: Resultssupporting
confidence: 92%
“…The β-globin gene cluster, an intergenic interval among the HBS1L and MYB genes (HMIP), and BCL11A are among these loci. The results of using ARMS-PCR showed that there are two alleles A and C with three genotypes AA, AC, and CC which are consistent with the previous studies[19,20]. The results of the frequency distribution of the A and C alleles of the BCL11A gene showed that their distribution percentage was not equal among the βthalassemia major patient and control samples, where the A allele percentage in patients was 56%, while in the control it was 52% and the…”
supporting
confidence: 89%
“…A possible reason is that the coinheritance of α-thalassemia 1 leads to mild β-thalassemia; thus, these patients were not found in a hospital-based sample collection ( 35 ). Furthermore, several genetic markers in the HBB cluster ( 10 , 15 , 17 , 51 ), BCL11A ( 15 , 17 , 19 ), and HBS1L - MYB ( 15 , 17 ) have been associated with fetal hemoglobin and disease severity in several populations. In addition, mutations in human Krüppel-like factor 1 ( KLF1 ) were found to be associated with increased fetal hemoglobin (Hb F) and hemoglobin A 2 (Hb A 2 ) ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, several SNPs located in the HBB cluster, HBS1L-MYB , and BCL11A have been identified by two genome-wide association studies with different platforms ( 17 , 18 ). Several informative SNPs for predicting disease severity in Thai and Malaysian β 0 -thalassemia/Hb E patients have recently been developed ( 19 ). In Thailand, the average life expectancy in β-thalassemia/Hb E patients is ~30 years ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…These gene alterations often cause either a decrease in β-globin synthesis or completely block synthesis [ 13 ]. For example, HbE/β-thalassemia is a G A substitution at the 26 position of the β-globin gene and replaces Glu with Lys, resulting in a decrease in the β-globin chain [ 14 , 15 , 16 , 17 ]. As such, 1–3% of the people in Southern China carry a β-thalassemia allele and over 20 β-thalassemia mutations have been reported in the Chinese population [ 18 ].…”
Section: Introductionmentioning
confidence: 99%